2022
DOI: 10.1155/2022/1591507
|View full text |Cite
|
Sign up to set email alerts
|

The Anion Gap and Mortality in Critically Ill Patients with Hip Fractures

Abstract: Objectives. Epidemiological evidence suggests that anion gap (AG) has been reported to serve as an independent predictor for mortality in different diseases. We studied the effect of AG on both short and long-term mortalities in critically ill patients with hip fracture. Methods. A large clinical database was utilized to perform retrospective cohort analysis. AG was subdivided into three groups. The Cox proportional hazards regression model was employed to approximate the hazard ratio (HR) with a confidence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Leskovan et al, through a retrospective study, demonstrated that an AG level exceeding 16mmol/L was significantly associated with unfavorable clinical outcomes in elderly trauma patients [ 23 ]. Zhang et al showed that patients with critical hip fracture and AG>12.5mmol/L had a 1.7-fold higher 30-day mortality rate compared to those with AG≤12.5mmol/L [ 24 ]. Trauma-related morbidity and mortality are frequently associated with hemorrhage, shock, tissue hypoperfusion resulting in metabolic acidosis and microcirculatory dysfunction, which could further lead to complications such as acute kidney injury (AKI), acute traumatic coagulopathy (ATC), adult respiratory distress syndrome (ARDS), ultimately culminating in fatality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Leskovan et al, through a retrospective study, demonstrated that an AG level exceeding 16mmol/L was significantly associated with unfavorable clinical outcomes in elderly trauma patients [ 23 ]. Zhang et al showed that patients with critical hip fracture and AG>12.5mmol/L had a 1.7-fold higher 30-day mortality rate compared to those with AG≤12.5mmol/L [ 24 ]. Trauma-related morbidity and mortality are frequently associated with hemorrhage, shock, tissue hypoperfusion resulting in metabolic acidosis and microcirculatory dysfunction, which could further lead to complications such as acute kidney injury (AKI), acute traumatic coagulopathy (ATC), adult respiratory distress syndrome (ARDS), ultimately culminating in fatality [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“… 17 Recent retrospective studies have shown that elevated AG is associated with increased mortality in ICU patients with aortic aneurysm, 7 AKI requiring CRRT, 9 cardiogenic shock, 10 acute pancreatitis 11 and hip fractures. 12 Moreover, other studies have examined the correlation between AG and mortality in ICU patients. Wang et al 18 found that high AG (>14mmol/L) within 48 hours after tissue plasminogen activator (rtPA) treatment in patients with cerebral infarction was linked to significantly higher overall, 1-year, and 4-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Recent studies have shown that a high AG level is associated with increased mortality in ICU patients with conditions such as aortic aneurysm, 7 sepsis, 8 acute kidney injury(AKI) requiring continuous renal replacement therapy(CRRT), 9 cardiogenic shock, 10 acute pancreatitis 11 and hip fractures. 12 …”
Section: Introductionmentioning
confidence: 99%
“…Features of the tumor microenvironment heavily affect disease biology and may affect responses to systemic therapy [ 52 55 ]. Previous studies demonstrated that LDHA was involved in the development of cancer through multiple signal pathways, including AKT/ mammalian target of rapamycin (mTOR), the c-Jun NH (2)-terminal kinase (JNK) and RIG-I like receptor signal pathway [ 56 58 ]. Besides, we found LDHA also promoted cancer progression through being involved in the cell cycle and DNA replication.…”
Section: Discussionmentioning
confidence: 99%